2021
DOI: 10.21608/jaauth.2021.88798.1219
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Ethnic Restaurant Menu Visual Appeal and Informativeness on Customers’ Desire to Order

Abstract: As restaurant menus play a critical role in customers' perceptions and behavioral intentions, this study examined the effect of ethnic restaurants' menus' visual appeal and informativeness on customers' perceived authenticity, quality, and desire to order. This study also examined the mediating role of the menus' informativeness between the menus' visual appeal and customers' perceived authenticity. Data were obtained from 416 customers who had visited an ethnic restaurant one month prior to the data collectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
0
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 67 publications
(86 reference statements)
1
0
0
3
Order By: Relevance
“…Additionally, consumer judgments of taste and food items in general may be influenced by visual appeal (Hutchings, 1994;Imram, 1999;Kostyla et al, 1978). As a further confirmation of the above study, Alotaibi and Alshiha (2021) showed that eye-catching menu designs have a beneficial effect on client demand and the perception of authenticity. Accordingly, the visual assessment of food as well as the right images can elicit strong visceral responses (mainly hunger) from viewers.…”
Section: Hypothesis Development 31 Menu Visual Appeal (Mv) and Desire...supporting
confidence: 64%
“…Additionally, consumer judgments of taste and food items in general may be influenced by visual appeal (Hutchings, 1994;Imram, 1999;Kostyla et al, 1978). As a further confirmation of the above study, Alotaibi and Alshiha (2021) showed that eye-catching menu designs have a beneficial effect on client demand and the perception of authenticity. Accordingly, the visual assessment of food as well as the right images can elicit strong visceral responses (mainly hunger) from viewers.…”
Section: Hypothesis Development 31 Menu Visual Appeal (Mv) and Desire...supporting
confidence: 64%
“…Menü içeriği de menü görsel çekiciliği kadar bireylerin satın alma niyetlerini etkileyen önemli bir kriterdir. Besin hazırlama yöntemlerine ve besin ögelerine ilişkin bilgiler içeren menüler bireylerin yemek seçimlerini olumlu yönde etkilemektedir 16 . Menü içeriklerine yönelik yapılan bir çalışmada, işletmede menü kartı kullanımı ile müşterilerin en fazla menü içeriği, en az kartın fiziksel özelliklerinden etkilendiği saptanmıştır.…”
Section: Araştırmanınunclassified
“…Kadınların görsel algı ve açıklık, erkeklerin ise çeşitlilik faktöründen etkilendiği belirlenmiştir 18 . Bu çalışmada, menü içeriklerinin yeterliliğinin kadınlarda çevrim içi yemek siparişi verme durumunu erkeklere göre daha fazla etkilediği belirlenmiştir (p<0,01) ve bulgular daha önce yapılan çalışmaların sonucunu destekler niteliktedir 9,16 . Buna karşın menü içerik yeterliliği açısından çevrim içi yemek siparişi verme sıklığının anlamlı olmadığı gözlenmiştir (p>0,05).…”
Section: Araştırmanınunclassified
See 1 more Smart Citation